At home in Asia? Sydney's Chinatown and Australia's 'Asian Century'. (May 2016) - Ang, Ien
It is widely recognised that the 21st century is seeing a geopolitical shift in global power relations towards Asia, particularly China. This has led Australia to officially embrace Asia as its regional home. But the neoliberal economic logic underpinning this embrace leads to a narrowly transactional conception of Australia's relationship to Asia, governed by an opportunity/threat dichotomy. By contrast, this article describes Sydney's Chinatown today as an increasingly hybrid, porous and transnational space of uneven and mixed-up, embodied Asian-Australianness. Juxtaposing the dynamic on-the-ground reality of this contemporary Chinatown with government discourse on Australia's relationship to Asia, as exemplified by the 2012 White Paper Australia in the Asian Century, illuminates that Australia is not yet at home in Asia.